2011
DOI: 10.1007/s00436-011-2545-7
|View full text |Cite
|
Sign up to set email alerts
|

First report on susceptibility of wild Aedes aegypti (Diptera: Culicidae) using Carapa guianensis (Meliaceae) and Copaifera sp. (Leguminosae)

Abstract: Oils of Carapa guianensis and Copaifera spp. are well known in the Amazonian region as natural insect repellent, and studies have reported their efficiency as larvicide against some laboratory mosquito species. However, in wild populations of mosquitoes, these oils have not yet been evaluated. Thus, the objective of this study was to investigate their efficiency as larvicide in wild populations of Aedes aegypti with a history of exposure to organophosphate. The susceptibility of larvae was determined under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Hence, there has been an increasing interest in the development of alternative methods of mosquito control which are less hazardous to humans and other living organisms. In this regard, plantderived compounds have emerged as good candidates, not only as new effective tools in vector management but also as environmentally safer agents (Garcez et al 2009;Govindarajan et al 2011;Kalaivani et al 2011;Prophiro et al 2011;Kanis et al 2011). The present study evaluated the effect of a novel herbal formulation PONNEEM prepared from A. indica and P. glabra oils to minimize human vector mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, there has been an increasing interest in the development of alternative methods of mosquito control which are less hazardous to humans and other living organisms. In this regard, plantderived compounds have emerged as good candidates, not only as new effective tools in vector management but also as environmentally safer agents (Garcez et al 2009;Govindarajan et al 2011;Kalaivani et al 2011;Prophiro et al 2011;Kanis et al 2011). The present study evaluated the effect of a novel herbal formulation PONNEEM prepared from A. indica and P. glabra oils to minimize human vector mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
“…total mortality at a concentration of 0.5 mg mL -1 (Table I) and lethal concentrations (LC) at lower dilutions (Table II (Prophiro et al 2012, Trindade et al 2013). The second major toxicity was obtained in ethanol extract of P. hispidum leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this paper present a better adulticide activity for M. greenmaniana essential oil in comparison with metanolic and aqueous extracts. There have been just few studies regarding botanical products that have revealed the adulticide effect against sandflies in comparison with mosquitoes (Amóra et al 2009;Pandey et al 2009;Khandagle et al 2011;Pitarokili et al 2011;Prophiro et al 2012). This is probably due to the difficulties of maintenance and availability of sandfly colonies (Yaghoobi-Ershadi et al 2006).…”
Section: Discussionmentioning
confidence: 95%